6xy*5xy+5x=

Simple and best practice solution for 6xy*5xy+5x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6xy*5xy+5x= equation:


Simplifying
6xy * 5xy + 5x = 0

Reorder the terms for easier multiplication:
6 * 5xy * xy + 5x = 0

Multiply 6 * 5
30xy * xy + 5x = 0

Multiply xy * xy
30x2y2 + 5x = 0

Reorder the terms:
5x + 30x2y2 = 0

Solving
5x + 30x2y2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '5x'.
5x(1 + 6xy2) = 0

Ignore the factor 5.

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(1 + 6xy2)' equal to zero and attempt to solve: Simplifying 1 + 6xy2 = 0 Solving 1 + 6xy2 = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 6xy2 = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 6xy2 = 0 + -1 6xy2 = 0 + -1 Combine like terms: 0 + -1 = -1 6xy2 = -1 Divide each side by '6y2'. x = -0.1666666667y-2 Simplifying x = -0.1666666667y-2

Solution

x = {0, -0.1666666667y-2}

See similar equations:

| f(-3)=9-4 | | t^2+11+24=0 | | 2(r-7)-(r-8)=3 | | 7+25=18+x | | X-3+2x=x+5 | | 7(4x-2)=5(2-x) | | x+25+x+-5=90 | | (2.4)(2.0)=(X)(0.5) | | 2(3.14)14= | | -(x+8)=-9x+56 | | (2c+5)(c+4)=0 | | 7+3y=18+x | | 3e-x-1=5 | | -16x^2+80= | | log(y)=1.9747log(x) | | 69x+9y=900 | | y=x^2+49 | | 6z-12z=1-18 | | 11n+9=6n+44 | | (9*4)-5=9*(4-5) | | -6h+4=-10h+16 | | 10p(4/5p) | | 5x+10-3x-3= | | y=4x^2+12x-5 | | -8x-18=-146 | | 4t-2=6t+6 | | -16x^2+80x= | | -5x*2x= | | x=1.8*x+32 | | 2x+14=-6x+34 | | a(n)=12+(n-1)(3) | | -6h+4=-10h+6 |

Equations solver categories